KARAKTERISTIK LINGKUNGAN PERAIRAN HABITAT BENIH DAN INDUK IKAN KERAPU DI PERAIRAN PANGKEP, SULAWESI SELATAN - Aliah, Ratu Siti; Amarullah, M. Husni; Sachoemar, Suhendar I. (Jurnal Hidrosfir Indonesia, 2007)
The environmental characteristics of seed and broodstock of the grouper, a reef fish species was investigated in the Pangkep water area, South Sulawesi to understand the water quality of the physical and chemical parameters condition. The environment of the Pangkep area was found in a good condition and it is suitable for habitat of the grouper as a reef fish though in some area the reef has degraded due to the utilization of an illegal fishing devise such bomb and cyanide. But application of the local wisdom in some area of Pangkep has succeeded in protecting the reef and fish population to serve the life of the islands people.Keywords: The environmental characteristics, seed and broodstock, grouper, Pangkep